Two Different Primary Tumors in the Same Brain-A Case Report and Review of the Literature - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2014)
Double primary brain tumors are very rare. A 77-year-old man admitted to our clinic due to headache and urinary incontinence. After radiological evaluation, double tumors in different lobes were observed. Stereotactic biopsy from the frontal lesion was managed, because of the patient's age and poor medical status. Histopathological diagnosis was glioblastoma. The other unresected parietal tumor was benign meningioma depending on MR images. Postoperative radiotherapy and chemotherapy were given. In this case report, a rare entity of coexistent double tumors is discussed with thorough literature review.
Keywords: Primary brain tumor; double tumor; meningioma; glioblastoma; stereotactic biopsy; GLIOBLASTOMA-MULTIFORME; MENINGIOMA; PATIENT